Manifest Gravitational Duality Near Anti de Sitter Space-Time - Hörtner, Sergio (Frontiers in Physics, 2019)
We derive a manifestly duality-invariant formulation of the Arnowitt-Deser-Misner action principle linearized around anti de Sitter background. The analysis is based on the introduction of two symmetric potentials –on which the duality transformations act– upon resolution of the linearized constraints, along the lines of previous works focusing on Minkowski and de Sitter backgrounds. Gauge freedom is crucially exploited to solve the constraints in this manner so convenient for exhibiting duality invariance, which suggests a delicate interplay between duality and gauge symmetry.